A comparison study on polymeric nanocomposite foams with various carbon nanoparticles: adjusting radiation time and effect on electrical behavior and microcellular structure. Issue 3 (3rd July 2022) - Aghvami-Panah, Mohammad; Wang, Ao; Panahi-Sarmad, Mahyar; Esfahani, Seyed Armin Seyed; Seraji, Amir Abbas; Shahbazi, Mehrnaz; Ghaffarian, Reza; Jamalpour, Seifollah; Xiao, Xueliang
ABSTRACT: The effect of carbon black (CB), carbon nanotube (CNT), and graphene (G) on foaming, electrical conductivity (EC), and electromagnetic interference (EMI) shielding of polystyrene (PS) foam that has been produced via microwave heating operation and supercritical carbon dioxide (CO2 ) was studied. Foams containing 1 wt %, CNT, and G reached over 90% porosity after 30 s and 3 min radiation time, respectively; however, PS/CB foam did not expand properly even after 3.5 min. In addition, the expansion ratio of PS/CB and PS/G was one-sixth and one-half of PS/CNT, respectively – due to the great CNT's ability to convert microwave radiation to heat. EC of solid and porous nanocomposites has been increased via raising filler content; however, PS/CNT displayed the highest value at the same volume fractions. This ascending trend could not endure during foaming, so a remarkable optimum-point has been observed for nanocomposite foams. Eventually, EMI-shielding properties of solid and foam nanocomposites were discussed. Graphical Abstract: uf0001